1991
DOI: 10.1104/pp.96.4.1157
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dimethyl Sulfoxide to Detect Hydroxyl Radical during Bacteria-Induced Hypersensitive Reaction

Abstract: Excess active oxygen is generated during the hypersensitive reaction (HR), an incompatible reaction of plants to bacterial pathogens. During HR, lipid peroxidation correlates chronologically with production of the oxygen species, superoxide (02-). However MO) seedlings were grown in a growth chamber at 23 to 270C with a photoperiod of 14 h/l0 h light/ dark. The seedlings were grown in vermiculite in plastic trays with cheesecloth covering aeration holes in the bottom. The plants were watered daily from below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Alternatively, AO species may be able to initiate a lipid peroxidation process in the plant tissues. This has already been described after elicitation (Rogers et al, 1988;Peever and Higgins, 1989;Vera-Estrella et al, 1992) or during incompatible plantlmicroorganism interactions (Keppler and Novacky, 1986;Adam et al, 1989;Popham and Novacky, 1991). The release of signals arising from this early peroxidative event has been postulated (Rogers et al, 1988) and has also been supported recently by studies demonstrating that peroxidized fatty acid metabolites may participate as intracellular messengers in the signaling system that activates various plant defense pathways (Li et al, 1991;Farmer and Ryan, 1992).…”
mentioning
confidence: 78%
“…Alternatively, AO species may be able to initiate a lipid peroxidation process in the plant tissues. This has already been described after elicitation (Rogers et al, 1988;Peever and Higgins, 1989;Vera-Estrella et al, 1992) or during incompatible plantlmicroorganism interactions (Keppler and Novacky, 1986;Adam et al, 1989;Popham and Novacky, 1991). The release of signals arising from this early peroxidative event has been postulated (Rogers et al, 1988) and has also been supported recently by studies demonstrating that peroxidized fatty acid metabolites may participate as intracellular messengers in the signaling system that activates various plant defense pathways (Li et al, 1991;Farmer and Ryan, 1992).…”
mentioning
confidence: 78%
“…Lipoperoxidation was monitored by the spectrophotometric determination of MDA using thiobarbituric acid according to Popham and Novacky (1991). Plant material (1 g FM) was homogenized in 2 cm 3 of trichloroacetic acid, TCA (10 %, m/v) and centrifuged at 15 000×g for 20 min.…”
Section: Enzymatic Activities and Lipid Peroxidation Analysismentioning
confidence: 99%
“…Using the dye-binding technique, various investigators have shown that leaves exposed to paraquat in the light produces hydroxyl radicals in plant tissues (12,14,15,17,18). The results obtained in this study with paraquat treatment are similar to rates of MSA formation reported by others using the dye-binding technique with various plant tissues ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Only 50-to 100-mg (fresh weight) samples were needed in the paraquat experiment. This is 10-fold smaller than was used with the dye-binding technique (12,14,15). The dye-binding approach requires the elimination of potentially interfering species (sample cleanup) from typical cell and tissue extracts that involve additional steps in the extract preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation